COMPATIBILITY STUDIES OF INTERSPECIFIC IN VITRO MICROGRAFTING OF AGARWOOD (Aquilaria malaccensis LAMK.) - NURITA TORUAN MATHIUS; JONNER SITUMORANG; DEWI RACHMAWATI RACHMAWATI; ANIDA (BIOTROPIA, 2008)
Aquilaria spp produced agarwood as nonwood  forest production, and has high economic value. A. malaccensis is susceptible to white rot diseases and termites. On the other hand most of the community plantations are a mixed culture with rubber trees, oil palms and with high risk of contamination causing white root diseases. Besides that, vegetative propagation by cuttings, stumping or air layering are still very difficult with low percentage of growth. The objectives of this research were to analyze the best suitable micrograft type, changes of SDS-PAGE protein band patterns of compatible and incompatible micrografts with several combinations of gaharu planlets in in vitro condition, and histology of union area between rootstocks and scion. The results showed that wedge or V type was the best of the micrografs. MS medium with the addition of 3 mg/L IBA was the best medium for gaharu planlet growth after micrografting. Acclimatization was conducted in husk chacoal and top soilÂ  (1:1) mediumÂ  and grown under plastic house of 70% shading with paranet. Compatible combination (Ac/Am) of micrografting showed that anatomy structure of union area is the same as anatomy structure of non micrograftd planlet. While incompatible (Gv/Am)Â  micrografting produced necrotic layer growth from pith and parenchymateous tissues of the wood in union areaÂ Â  alongÂ  the middle of radialÂ  shoot. Recovery period of union area between stocks and scion is initiated by callus formation from the pith and parenchymatous tissues of the wood. Callus will differentiate into mature cells or tissue and becomeÂ  combinedÂ  phloem and xylem vessels between rootstocks and scion. SDS-PAGE protein band pattern on compatible combination was the same as plants originated from seedlings. While, incompatible combination produced new protein bands with molecular weight around  21 and 30 kD. Key words : Agarwood, Aquilaria spp, micrografting in vitro, incompatible micrografting, SDS-PAGE protein, incompatible histology.